Characterization of Mucosal Immune-Related lncRNAs and mRNAs in a Mouse Model of Allergic Conjunctivitis - Zhang H; Zhang H; Leng Q; Zheng YJ (Journal of Inflammation Research)
Hong Zhang,1,2 Hongyu Zhang,3 Qing Leng,3 Ya Juan Zheng1 1Department of Ophthalmology, The Second Hospital of Jilin University, Jilin University, Changchun, Jilin, People’s Republic of China; 2Department of Ophthalmology, China-Japan Union Hospital of Jilin University, Changchun, Jilin, People’s Republic of China; 3Department of Immunology, College of Basic Medical Sciences, Jilin University, Changchun, People’s Republic of ChinaCorrespondence: Ya Juan Zheng, Email yjzheng@jlu.edu.cnBackground: Allergic conjunctivitis (AC) is a common inflammatory condition characterized by immune dysregulation in response to environmental allergens. Despite extensive research into general allergic mechanisms, the specific immunological features of the ocular mucosal microenvironment remain poorly understood. Investigating immune-related mRNAs and LncRNAs may provide insights into the mechanisms underlying AC and potential novel targets for therapeutic intervention.Methods: An AC model was established using female BALB/c mice sensitized with ragweed pollen. Conjunctival tissues from AC and control groups were pooled for RNA extraction, followed by Illumina sequencing. Differential gene expression was identified using DESeq2, and functional enrichment was analyzed using GO, KEGG, and GSEA. RT-qPCR validated results, while the Human Protein Atlas was used to assess protein expression.Results: A murine model of AC was successfully established, confirmed by progressively increasing clinical scores and significantly elevated scratching frequency. Transcriptomic analysis revealed significant differences in mRNAs and lncRNAs expression between AC and control groups. GO analysis indicated that both upregulated and downregulated genes were enriched in biological processes related to response to stimulus, immune system processes, signaling, and metabolic processes. KEGG analysis showed that upregulated genes were enriched in pathways such as steroid hormone biosynthesis, histidine metabolism, glycolysis/gluconeogenesis, and IL-17 signaling, while downregulated genes were involved in cytokine-cytokine receptor interaction and hematopoietic cell lineage. GSEA identified significant enrichment in inflammatory pathways, including MAPK, STAT1, and STAT2. Mucosal immunity-related genes such as Bpifa1, Lcn2, and Reg3g were upregulated in AC. Co-expression analysis also revealed several upregulated lncRNAs, including Stoml3-202 and Etohd2-205.Conclusion: This study is the first to systematically analyze immune-related mRNAs and LncRNAs in AC, identifying mucosal immunity molecules like Bpifa1 and Reg3g. These findings underscore the unique involvement of mucosal immunity in AC and provide potential new targets for immune modulation in ocular allergy treatment.Keywords: allergic conjunctivitis, lncRNA, transcriptomic analysis, immune-related genes